AN ANALYSIS OF COHESION DEVICES IN POLITICAL NEWS OF THE JAKARTA POST: A DISCOURSE ANALYSIS APPROACH: A DISCOURSE ANALYSIS APPROACH Zia Hisni Mubarak, mubarakzia@gmail.com, Universitas Putera Batam - zia hisni mubarak (BASIS (Bahasa dan Sastra Inggris), 2014)
Newspaper is one of an effective tool to deliverthoughts or even to get the information. The languageof journalism in the newspaper is related to the actionor opinion from people and it is conveyed into a text.This research is aimed at knowing the function of thetext by analyzing the text based on the Discourseanalysis. The researcher uses cohesion devices toanalyze the text of political news in an onlinenewspaper. This research is designed as a descriptiveresearch where the researcher conducts the researchin order to knowing the phenomenon in the field ofstudy. The researcher, then, analyze the text based onthe cohesion devices such as substitution, ellipsis,conjunction, reference and lexical cohesion. Theresult of this research shows that the text in an onlinenewspaper which is analyzed in this research has agood structure of cohesive